Estimation of Energy Levels of Contacts and Tribological Properties of Materials of Friction Pairs - Janahmadov, A.Kh.; Volchenko, N.A.; Javadov, M.Y.; Zhuravlev, D.Y.; Shasherina, S.A.; Romaniv, N.N. (Herald of Azerbaijan Engineering Academy, 2021)
Estimation of the energy levels of contacts of microprotrusions of friction pairs "shoe-disk" was carried out on a friction and wear machine SMTs-2. In this case, the block was made of ordinary Kh12MF steel, and the disk was diffusion-coated with a Ni-Cu alloy and reinforced by surface plastic deformation. Experimental studies carried out on four test cycles made it possible to obtain profiles of profilograms and use them to establish the types of contacts (ohmic, neutral and blocking) for the samples and their duration of action. Investigation of the tribotechnical properties of the "shoe-disk" friction pairs made it possible to determine: surface temperature, dynamic coefficient of friction and wear of the samples. At the same time, the influence of diffusion metallization and surface plastic deformation on the relative wear resistance and roughness of samples made of Kh12MF steel was established. The physical substantiation of the obtained parameters is given.